2009
DOI: 10.1038/msb.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for cellular decision‐making

Abstract: Stochasticity pervades life at the cellular level. Cells receive stochastic signals, perform detection and transduction with stochastic biochemistry, and grow and die in stochastic environments. Here we review progress in going from the molecular details to the information-processing strategies cells use in their decision-making. Such strategies are fundamentally influenced by stochasticity. We argue that the cellular decision-making can only be probabilistic and occurs at three levels. First, cells must infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
256
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(259 citation statements)
references
References 103 publications
(142 reference statements)
3
256
0
Order By: Relevance
“…Recent work has shown that biochemical networks have evolved to capture the multidimensional structure of diverse environments and thus form internal representations (through regulatory networks) that allow the prediction of environmental changes. For example, Tagkopoulos et al (17) provided evidence of anticipatory behavior of E. coli to changes in temperature and oxygen levels that occurred over evolutionary time scales (21,22). We examined the anticipatory ability of our rewired GTRNs by computing their optimality using transcriptomic fitness with the same set of genes used in the in silico evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that biochemical networks have evolved to capture the multidimensional structure of diverse environments and thus form internal representations (through regulatory networks) that allow the prediction of environmental changes. For example, Tagkopoulos et al (17) provided evidence of anticipatory behavior of E. coli to changes in temperature and oxygen levels that occurred over evolutionary time scales (21,22). We examined the anticipatory ability of our rewired GTRNs by computing their optimality using transcriptomic fitness with the same set of genes used in the in silico evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
“…cheaters), particularly in spatially unstructured populations [28]. Within a structured population of closely related individuals, however, cooperative traits can be favoured as a public good and facilitate the success of the entire population [29][30][31][32]. This principle of facilitation [33,34] has been shown in populations of various organisms, including bacteria [35], toxigenic cyanobacteria [36], amoeba [37] and yeast [38].…”
Section: Introductionmentioning
confidence: 99%
“…diffusion sensing | bacterial signaling | efficiency sensing | collective behavior | bacterial cooperation B acteria must often make regulatory decisions on the basis of limited information about their external world (1). In many bacteria, these decisions are aided by the secretion and detection of small diffusible molecules, in a process called quorum sensing (QS) (2,3).…”
mentioning
confidence: 99%